The Magnetic Resonance Imaging (MRI) Features in Diagnosing Tumefactive Demyelinating Lesion. - Foo, See Yun; Rahim, Nurul Hafidzah; Mohd Mustapha, Aida Widure Mustapha; Mohd Zaini, Noraini Rose (Journal Of Cardiovascular, Neurovascular & Stroke, 2022)
Background: A demyelinating lesion can present as a space occupying lesion in Magnetic Resonance Imaging (MRI) brain. Lesions that have diameter greater than 2 cm is referred as tumefactive demyelinating lesion. These lesions can mimic a brain tumor, namely glioma or primary central nervous system lymphoma. Case presentation: We present two female patients over 30 years old who presented with limb weakness. Their MRI demonstrated typical appearance of a solitary, incomplete rim enhancing lesion that involved the subcortical white matter with minimal mass effect. Also, the rim of enhancement opened to the grey matter. Due to their typical appearance, biopsy was not performed. The lesions in both patients reduced in size upon follow up after treatment commencement and currently recovering. Conclusion: In this case report, we focus on discussing the MRI features of tumefactive demyelinating lesion and its main differentials, which are central nervous system lymphoma (CNSL) and glioma.